Latest Early Pleistocene remains of Lynx pardinus (Carnivora, Felidae) from the Iberian Peninsula: Taxonomy and evolutionary implications. (1st July 2016) - Boscaini, Alberto; Alba, David M.; Beltrán, Juan F.; Moyà-Solà, Salvador; Madurell-Malapeira, Joan
Abstract: The Iberian lynx ( Lynx pardinus ) is a critically endangered felid that, during the last fifty years, has been subject to an intensive conservation program in an attempt to save it from extinction. This species is first recorded at ca. 1.7–1.6 Ma (late Villafranchian, late Early Pleistocene) in NE Iberian Peninsula, roughly coinciding with the large faunal turnover that occurred around the middle to late Villafranchian boundary. Here we describe the largest collection of L. pardinus remains available to date from the Iberian late Early Pleistocene (Epivillafranchian), including localities from the Vallparadís Section (Vallès-Penedès Basin, NE Iberian Peninsula) and Cueva Victoria (Cartagena, SE Iberian Peninsula). The morphology and biometry of the studied material attests to the widespread occurrence of L. pardinus in the Mediterranean coast of the Iberian Peninsula since the latest Early Pleistocene, i.e., about 0.5 million years earlier than it was generally accepted (i.e., at the beginning of the Middle Pleistocene). Based on the features observed in the large sample studied in this paper, we conclude that Lynx spelaeus is a junior synonym of L. pardinus and further propose to assign all the Epivillafranchian and younger fossil lynxes from SW Europe to the extant species L. pardinus . Due to the arrival of the Eurasian lynx ( Lynx lynx ) into Europe at the beginning of the Late Pleistocene, the attribution of specimens younger than MIS 5e to either this species or L. pardinus solely on morphological grounds has proven equivocal. Here we discuss the main diagnostic features of both species of European lynxes and further review their evolutionary history and paleobiogeography throughout the Pleistocene. Highlights: We describe the largest available collection of lynx remains from the Early Pleistocene of Iberia. We conclude that the Iberian lynx was widespread across the Iberian Peninsula since 1.0 Ma. We review the diagnostic features of both extinct and extant European lynx species. We conclude that Lynx spelaeus is a junior subjective synonym of Lynx pardinus . The evolutionary history and paleogeography of European lynx species in the Pleistocene is reviewed.